Injury prevention of hamstring injuries through exercise interventions - Raya-Gonzalez, J.; Castillo, D.; Clemente, F. M. (The Journal of Sports Medicine and Physical Fitness, 2021)
INTRODUCTION: Hamstring injuries are the most prevalent time-loss injuries in sport, mainly in those modalities characterized by high-intensity and short-term actions, especially accelerations and decelerations during high-speed running. Expanding the knowledge about this type of injury and its preventive programs could be a key strategy to reduce the hamstring injury incidence. Thus, this review aimed to study the effectiveness of different preventive programs based on exercise interventions on reducing the hamstring injury incidence in athletes. EVIDENCE ACQUISITION: An umbrella review was conducted through of PubMed/MEDLINE, Scopus, SPORTDiscus, Web of Science, Cochrane Library and Physiotherapy Evidence Database databases. The methodological quality of the included systematic reviews was assessed through the Assessing the Methodological Quality of Systematic Reviews 2 and the quality of the evidence was evaluated using the modified Grading of Recommendations Assessment, Development and Evaluation principles. EVIDENCE SYNTHESIS: Eight systematic reviews and meta-analysis (40 primary studies) met the inclusion criteria, which included interventions based on eccentric strength, Nordic hamstring, proprioceptive training, stretching, FIFA11 and combined programs. From the qualitative synthesizes, three studies showed that eccentric-based training programs were effective; seventeen studies reported that Nordic hamstring-based programs were effective; three studies observed that stability training-based interventions were effective; two studies indicated that flexibility were effective; three studies claimed that FIFA11+based programs were effective; and two studies reported that combined programs were effective. CONCLUSIONS: Exercise is a key strategy to reduce the hamstring injury incidence, being programs based on eccentric strength mainly by means of Nordic hamstring exercise, and on stability training, those programs which reported greater effectiveness.